(untitled) (Orfeu, 2020)
The present study aims to bring up some questions about my work with contemporary music to dialogue with the academic environment, whether as a composer, performer or instrumentalist, the subjects are: naïf art, playful use of the Übermensch concept, interpreter as an active/passive agent, Stanislavsky System used in compositions and the attempt to attract more audiences to experimental music without appealing to kitsch aesthetics. I bring other composers to this discussion, reflections on my compositions and approaches that range from psychoanalysis to the technological-economical analysis of the period we are in. I also dedicate an item to briefly comment on a selection of my works. In the end, all these questions result in the great anguish of my generation: The impossibility of defining what music is today. This is definitely a subject that will still have a lot of discussion and that seems to be far from being solved (if it ever will be).